Analysis of the Economic Development of the Community of Purun Village, Banjarbaru City, 2010-2023 - Farah Mu’thia; Fitri Mardiani; Syaharuddin Syaharuddin (STKIP Taman Siswa Bima, 2024)
Purun Village is one of the climate villages formed by the government and represented by the Head of Palam, Agus Adrian on July 1, 2016. This study aims to determine the beginning of the establishment of Purun Village in Banjarbaru City and the development of the economic life of the community in Purun Village since 2010-2023. This study uses a historical method, which consists of four stages, namely the first heuristic, the second source criticism, the third interpretation, and the fourth historiography. The results of the study show that before the existence of Purun Village, the community there had been carrying out purun weaving activities even though only in the form of baskets and purun mats, after the formation of Purun Village in July 2016, more and more craftsmen participated in weaving purun. Purun Village has become a village that can support the economy of craftsmen with sales not only limited to the surrounding area but has spread internationally. The conclusion obtained is that over time, Purun Village has developed to foreign countries, thanks to the persistence of the female purun craftsmen and the encouragement from the Banjarbaru government which has greatly influenced the development of Purun Village, Palam Subdistrict.